Design development of an economic solar paraboloidal concentrator for industrial process heat generation - Kumar, Sandeep; Mahavar, Sunita; Mawire, Ashmore; Ruivo, Celestino Rodrigues (Energy conversion and management, 2023)
•An economic solar paraboloidal concentrator design is developed.•Experimental tests were conducted.•A comparative study with a commercial system is performed.•New characteristic parameters are defined and computed. The design parameters, structure design and component materials of a solar dish concentrator system extensively affect its performance, operation, cost and maintenance. The present paper addresses all these subjects and introduces an economic solar paraboloidal concentrator (ESPC). The development of ESPC is based on a methodology that covers the design, performance and economic analyses. The structural novelty of the ESPC includes good ground clearness, compact dual axis tracking based on electric actuator and structure innovation for good stability. The stagnation temperature of ESPC is found to be around 400 °C. A new optical performance parameter based on the stagnation temperature is also introduced. The sensible heating test with silicone oil reveals that a temperature around 300 °C could be achieved. The maximum thermal efficiency of the system is found to be 57%. A commercial solar paraboloidal concentrator (CSPC) is also tested for the comparative study. The sensible fluid flow test of heating 50 L of water from 23 °C to 70 °C demonstrates that one heating cycle periods of ESPC and CSPC are 155 and 70 min., respectively. Although the heating cycle period is larger for the ESPC, the cost of the ESPC is 58% lesser than CSPC. Consequently, ESPC presents a lesser payback period than CSPC.